2005
DOI: 10.1007/s11104-004-0185-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of Calamagrostis communities in preventing soil acidification and base cation losses in a deforested mountain area affected by acid deposition

Abstract: The effects of grass growth and N deposition on the leaching of nutrients from forest soil were studied in a lysimeter experiment performed in the Moravian-Silesian Beskydy Mts. (the Czech Republic). It was assumed that the grass sward formed on sites deforested due to forest decline would improve the soil environment. Lysimeters with growing acidophilous grasses (Calamagrostis arundinacea and C. villosa), common on clear-cut areas, and with unplanted bare forest soil were installed in the deforested area affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Peřina and Květ (1975) reported an intensive withdrawal of all nutrients by the reed grass. The accumulation of nutrients in the reed grass biomass and the elimination of adverse processes connected with soil acidification by reed grass stands were confirmed also in open forests and on a clear-cut area (Fiala et al 2005;Mládková et al 2005). On the other hand, the statistical tests in our study showed no differences in the chemistry of top soil horizons between the reed grass and wavy hair grass variants.…”
Section: Discussionsupporting
confidence: 77%
“…Peřina and Květ (1975) reported an intensive withdrawal of all nutrients by the reed grass. The accumulation of nutrients in the reed grass biomass and the elimination of adverse processes connected with soil acidification by reed grass stands were confirmed also in open forests and on a clear-cut area (Fiala et al 2005;Mládková et al 2005). On the other hand, the statistical tests in our study showed no differences in the chemistry of top soil horizons between the reed grass and wavy hair grass variants.…”
Section: Discussionsupporting
confidence: 77%
“…5). Fiala et al (2005) observed, that Calamagrostis villosa efficiently accumulates N in the biomass and can in this way reduce N losses from ecosystem during the growth season. Our results further suggest that dead grass leaves release the accumulated N in the form of DIN, mainly NH 4 into the soil in the early stage of decomposition and can temporarily increase NH 4 flux into the soil in autumn and winter period.…”
Section: S501mentioning
confidence: 92%
“…Sward grass vegetation can also decrease soil acidity and the loss of base cations (Fiala et al, 2005). This suggests that some species of understory vegetation can partly eliminate negative processes associated with soil acidification and positively affect the reduction of nutrient losses from the soil (Fiala et al, 2005). Contradictory results were found by Šantrůčková et al (2006), showing that vegetation cover of Calamagrostis villosa possibly contributed to high N flux from the litter in the spruce forest of the Bohemian Forest.…”
Section: Introductionmentioning
confidence: 88%
“…It has been shown that grass understory vegetation can serve as an important sink of atmospheric nitrogen (Holub, 1999). Sward grass vegetation can also decrease soil acidity and the loss of base cations (Fiala et al, 2005). This suggests that some species of understory vegetation can partly eliminate negative processes associated with soil acidification and positively affect the reduction of nutrient losses from the soil (Fiala et al, 2005).…”
Section: Introductionmentioning
confidence: 99%